Postoperative radiotherapy (adjuvant, salvage) after radical prostatectomy - Milecki, Piotr; Kwias, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 2003)
Currently radical prostatectomy (RP) remains the standard mode of treatment for patients with locally and localized stage of prostate cancer. On the other hand, after radical prostatectomy approximately 50% of patients have postoperative positive margin. Therefore, the implementation of the effective mode of adjuvant treatment after RP is warranted for selected patients with adverse prognostic factors. Currently available data, which evaluated the effectiveness of radiotherapy after RP are based on retrospective studies. These studies indicated that post-operative radiotherapy reduced the local recurrence rate but the influence on the patient’s survival is unknown. Generally, the following factors are considered as prognostic for failure: the presence of pathologic stage T3 (pT3), positive surgical margin, preoperative PSA>25 ng/ml, metastases to lymph nodes, Gleason>7. Radiotherapy is performed as typical adjuvant radiotherapy in the case of pT3 or positive margin without biochemical failure. This mode of treatment is efficient and gives excellent local control rate but without marked influence on the overall survival of patients. Another strategy, which is considered after RP, is salvage radiotherapy. This mode of treatment is introduced when the rising level of PSA and/or the pathological recurrence mass in the tumor bed occurs. The efficacy of the salvage radiotherapy is lower than the classical adjuvant radiotherapy. The questions about the following issues still need to be answered: timing of radiotherapy, optimal dose, treatment technique, involved target for radiotherapy, and the role of the adjuvant hormonal therapy. The last issue is now being evaluated in the randomized clinical trial. In summary, currently until outcomes from well conducted randomized trials are available patients after radical prostatectomy with adverse significant factors for local recurrence or/and increased level of PSA should be considered for postoperative radiotherapy.